Odpowiedź :
[tex]a) \: 2x + 5 = - 3x + 5 \\2x + 3x = 5 - 5 \\ 5x = 0 \: \: \: \: | \div 5 \\ x = 0[/tex]
[tex]b) \: - 7y = 84 \: \: \: | \div ( - 7) \\ y = - 12[/tex]
[tex]c) \: - 2x + 3 - 4x = 6 \\ - 2x - 4x = 6 - 3 \\ - 6x = 3 \: \: \: | \div ( - 6) \\ x = \frac{3}{ - 6} = - \frac{1}{2} [/tex]
[tex]d) \: 8a - 6 = 20 + a \\ 8a - a = 20 + 6 \\ 7a = 26 \: \: | \div 7 \\ a = 3 \frac{5}{7} [/tex]
[tex]e) \: 2(4x + 3) = - 18 \\ 8x + 6 = - 18 \\ 8x = - 18 - 6 \\ 8x = - 24 \: \: | \div 8 \\ x = - 3[/tex]
[tex]g) \: - x + 4 = 2x - 12 \\ - x - 2x = - 12 - 4 \\ - 3x = - 16 \: \: | \div ( - 3) \\ x = 5 \frac{1}{3} [/tex]
[tex]f) \: 35 - 4b = 24 - b \\ - 4b + b = 24 - 35 \\ - 3b = - 11 \: \: | \div ( - 3) \\ b = 3 \frac{2}{3} [/tex]